Vzyaimosvyaz ritma i tempa biomekhanicheskoj struktury sportivnykh dvizhenii - Kozlov, I. M.; Samsonova, A. V.; Tomilov, V. N. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The authors have carried out the analysis of features of the biomechanical structures in cyclic and acyclic movements on the basis of the research. Structures of distribution of muscular efforts have the specific rhythmic figure. It can be presented as the separate step. Its feature is the presence of the strong and weak parts (the maximal and minimal efforts). The change of the rate of movement results in the change of quantities of these parts and the ratio of sizes and time intervals between them - the arrangement of stresses during the performance of exercise. The simplification of a rhythmic figure with the increase of rate can testify to properties of complex, integrative system having the quality of self-organizing inherent to the supporting-moving apparatus.